Experimental study of large-scale vortices range in turbulent free jet - Isatayev, S.; Toleuov, G.; Isatayev, M.; Esenalina, K. (Recent Contributions to Physics, 2012)
The aim of this work is the experimental investigation of the coherent structure of turbulence in a three-dimensional jet, their maximum range. It was found that the jet streams originally appeared vortices can decay into smaller and mutually interacting with each other and merge to form a large conglomerate of eddies that retain their individuality until about the decay of the jet in the direction of flow. Experimentally, we have shown that the maximum frequency of turbulent fluctuations do not exceed the frequency of the primary large-scale vortices formed in the initial section of the jet stream.